PENYELESAIAN WANPRESTASI DALAM PERJANJIAN SEWA BELI TANAH DAN BANGUNAN MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA - Ayu Herlin Norma Yunita (Nusantara Hasana Journal, 2022)
This study examines the Decision of the Supreme Court of the Republic of Indonesia Number 931 K/Pdt/2019. In this decision the Defendant who does not want to carry out his obligations, namely signing the Sale and Purchase Deed in accordance with the contents of Article 14 of the said Agreement, so that the Plaintiff suffers a loss, namely not getting legal certainty over the house and land in question and cannot carry out the transfer process for the house and land in question. The research method carried out by the author is normative research, namely research from in action on the validity of normative law. This research is descriptive in nature, namely research that seeks to describe the solution of existing problems based on legal material, so it presents the legal material and then analyzes and interprets it. The results of this study conclude that a) If there has been a breach of contract, then the steps that can be taken are to subpoena/reprimand the act of breaking the promise. This subpoena/reprimand is useful to remind parties who have defaulted on obligations that must be fulfilled according to the agreement. To demand the cancellation of a contract and compensation from the debtor, the debtor must first default, and the default occurred due to his fault or negligence. This subpoena is regulated in Article 1238 of the Civil Code and Article 1243 of the Civil Code. b) The legal consequences in the Decision of the Supreme Court of the Republic of Indonesia No. 931 K/Pdt/2019 stated that the Defendant had committed an act of default or broke a promise. Sentencing the Defendant to immediately sign the Deed of Sale and Purchase of Land and Building with the Plaintiff before the Land Deed Making Officer (PPAT). Determine the Plaintiff to sign the Sale and Purchase Deed himself as the Seller and the Buyer, if the Defendant is not willing to sign the Sale and Purchase Deed.